The Ways and Methods of Expressing Voice in Armenian - MURADYAN, VIKTORYA (Bulletin of Yerevan University B: Philology, 2021)
Inheriting voice from Indo-European parent language, Armenian hasn't differentiated it with morphological indicators for a long time. In Old Armenian, it was possible to express the meaning of passive voice with some declination endings. In Middle Armenian the ու/վ/ւ affix was generally used as a passive voice indicator, which continued to be used in that function in New Armenian as well, however in Modern Eastern Armenian while defining the voice, besides ‘վ’ passive indicator, the semantics and the syntactic structure of the sentence also play a significant role. Several bases are concerned while defining the voice – morphological indicator, word-meaning, syntax application, the possibility of getting different, especially direct and indirect objects.